2009
DOI: 10.1161/hypertensionaha.109.130898
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Menstrual Cycle, Pregnancy, and Preeclampsia on Arterial Stiffness

Abstract: Abstract-Arterial stiffness and compliance are major predictors of adverse cardiovascular events and are influenced by female sex hormones, including estrogen and progesterone. The aim of this longitudinal study was to evaluate the effect of the menstrual cycle, normal pregnancy, and preeclampsia on central and systemic arterial stiffness. Ten healthy nulliparous women with regular menses were studied in the early and midfollicular, periovulatory, and luteal phases of a single menstrual cycle. Twenty-two primi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
158
5
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 47 publications
22
158
5
3
Order By: Relevance
“…We did not address this question in the present study; however, in their work, Robb et al 30 could show that PWV is not significantly affected by the periodical physiological changes of steroid hormones in women. Thus, in this particular case, the PWV is more than 2 standard deviations higher compared to the healthy population.…”
Section: Limitationsmentioning
confidence: 54%
“…We did not address this question in the present study; however, in their work, Robb et al 30 could show that PWV is not significantly affected by the periodical physiological changes of steroid hormones in women. Thus, in this particular case, the PWV is more than 2 standard deviations higher compared to the healthy population.…”
Section: Limitationsmentioning
confidence: 54%
“…In order to sustain the developing fetus, extensive cardiovascular adaptation occurs during pregnancy (Robb et al 2009a(Robb et al , 2009b. Increased production of endothelium-derived vasodilators is accompanied by enhancement of endothelial function and reactivity (Anumba et al 1999) and an increase in flow-mediated dilation of the brachial artery (Dorup et al 1999).…”
Section: Vascular and Fibrinolytic Functionmentioning
confidence: 99%
“…They revealed that AI reduced during late follicular and early luteal phase. Another study by Robb et al (2009) also observed that AI reduced during luteal phase when compared to periovulatory phase. The possible discrepancy in our result and theirs was probably due to different phases of menstrual cycle used to assess menstrual hormonal fluctuation.…”
Section: The Effects Of Menstrual Cycle On Aimentioning
confidence: 82%
“…Another study from Ounis-Skali et al (2006), which involved a comprehensive assessment of central and peripheral PWV, central waveform morphology, and central aortic pressure too showed no significant changes in BP and PWV throughout phases of the normal menstrual cycle. Study by Robb et al (2009), which studied ten healthy nulliparous women with regular menses in the early and midfollicular, periovulatory, and luteal phases of a single menstrual cycle showed no changed in PWV. Another study by Adkisson et al (2010) which measured PWV at early follicular, late follicular, early luteal and late luteal phase also found no changes.…”
Section: The Effects Of Menstrual Cycle On Pwvmentioning
confidence: 93%
See 1 more Smart Citation